International Experience of Legal Service Relations in the National Security Sphere: Issues of Implementation in Ukraine - Kudinov, Serhiy S.; Brovko, Nataliia I.; Stolbovyi, Volodymyr M. (Cuestiones Políticas, 2020)
The purpose of the document is to study the international experience of the development and operation of legal service relations in the field of national security and, furthermore, to elaborate proposals on the adoption of its best practices in Ukraine. The document aims to identify problems and improve current Ukrainian legislation dealing with public service and legal service relations in the field of national security. The main method was comparative. The following proposals are developed: the adoption of a single codified normative act to regulate legal service relations between all categories of public servants; the introduction of an open competition system for high-ranking officials; depoliticization of public service; implementation of international experience of legal regulation of service relations in the field of national security of Ukraine. In conclusion, the document materials can be of theoretical and practical value for academics investigating various aspects of the implementation of legal service relations and the sphere of national security in general, experts in the security and defense sector of Ukraine.